Taxation in Latin America : Structural Trends and Impact of Administration - Shome, Parthasarathi (IMF Working Papers; Working Paper ;, 1999)
From the mid-1980s to early 1990s, Latin American tax policy provided rich lessons for other reforming countries. Meaningful innovations led also to perceptible revenue gains. Later in the 1990s, tax policies began to drift. Shining examples of fundamental reform seemed to lose their luster. Revenue in terms of GDP also stagnated, partly reflecting over-reliance on consumption taxes and neglect of taxable capacity on incomes. The stagnation has been exacerbated by excessively simplified administrative practices. Based on these developments and on the limited taxability of internationally mobile capital, the paper anticipates a likely tax structure for the new century.